2019
DOI: 10.1039/c8ta09899a
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier transport dynamics in W/Mo-doped BiVO4: first principles-based mesoscale characterization

Abstract: First principles-based mesoscale characterization of electron transport in W/Mo-doped BiVO4 reveals the existence of “stabilization” regions around dopant sites. The stabilization regions decrease slightly the electron polaron mobility, albeit the overall electrode conductivity increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…However,t here still remains the key issue that carrier transport inside the BiVO 4 photoelectrode is too sluggish, making the water splitting performance quite low when light was illuminated from the ESI side. [18][19][20][21][22] Our previous work unveiled that the poor performance is mainly due to the slow,t rap-limited electron transport by investigating the performance difference between the light illumination from the ESI side and from the FTO side. [22] Recent advances disclosed that the poor majority carrier transport of BiVO 4 is caused by the formation of electron small polarons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However,t here still remains the key issue that carrier transport inside the BiVO 4 photoelectrode is too sluggish, making the water splitting performance quite low when light was illuminated from the ESI side. [18][19][20][21][22] Our previous work unveiled that the poor performance is mainly due to the slow,t rap-limited electron transport by investigating the performance difference between the light illumination from the ESI side and from the FTO side. [22] Recent advances disclosed that the poor majority carrier transport of BiVO 4 is caused by the formation of electron small polarons.…”
Section: Introductionmentioning
confidence: 99%
“…[15,27,28] To tackle the slow carrier transport issue,d opants were introduced, such as molybdenum and hydrogen. [16,18,20,29] Conceivably,amore direct and effective way to get to the root of the issue is to control the oxygen vacancy itself and, in doing so,toengineer the polaron hopping dynamics,b ut no effective method has been developed as yet.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Li's group suggested that W/Mo doping increased the carrier concentration and the conductivity of BiVO 4 by a density functional theory DFT + U method. [ 24 ] Nevertheless, multi‐element doping is difficult to be implemented in most cases because the operation steps are cumbersome, and normally requires expensive equipment such as ion implanter. [ 25,26 ] The even distribution and avoidance of phase separation during calcination also remain challenging when the mixture of precursors are used.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the poor charge transport ability, short carrier diffusion lengths (≈70 nm), and high charge recombination rates of BiVO 4 greatly limit its practical PEC performance. To address these problems, various strategies such as morphology design, element doping, host–guest heterojunctions and surface modifications are developed to enhance the performance . Nanostructured electrode design is one effective route to enhance the light absorption and charge transport ability.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, metal oxides such as TiO 2 , [5,6] Fe 2 O 3 , [7][8][9] and BiVO 4 [10][11][12] have been widely investigated as photoanodes for PEC water splitting due to the characteristics of excellent photoactivity, low cost, and good stability. [19][20][21][22][23][24] Nanostructured electrode design is one effective route to enhance the light absorption and charge transport ability. [13][14][15][16][17][18] Nevertheless, the poor charge transport ability, short carrier diffusion lengths (≈70 nm), and high charge recombination rates of BiVO 4 greatly limit its practical PEC performance.…”
mentioning
confidence: 99%